The Evolution of the Extended Comprehensive School Model and the Modern Profession-Oriented Teacher Education After World War II - Elstad, Eyvind (Springer International Publishing, 2023)
Abstract Despite the fact that the Nordic countries had very different experiences during World War II, cooperation intensified in the 1950s. The Nordic school model, with its emphasis on the child in focus, inclusion, equal opportunities for all, and an extended comprehensive and undifferentiated school system, emerged. The sorting of pupils into different tracks took place at age 15 or 16. The 1960s saw a significant expansion of the education systems, with the Swedish school model emerging as a paradigm for the other Nordic countries. With Finland’s success in the first comparative education studies, Finnish teacher education became the standard for teacher education in Iceland and Norway. Sweden follows more complex models for teacher education, while Danish teacher education is an outlier from a Nordic comparison perspective. While Finnish teacher education has shown stability, frequent changes in models of teacher education in the other Nordic countries are typical. In public discourse, crises in teacher education are a recurring theme. These crises concern criticism of the quality of applicants, what student teachers learn, and insufficient graduate production. The problems facing teacher education are varied, but where they occur, they are dire; there are no simple solutions to the challenges that currently exist.